In the eye of the observer. Western baltic cod under a transdisciplinary focus - Schwermer, Heike (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2021)
The unsustainable exploitation of fish stocks is one of the greatest anthropogenic impacts on oceans and coastal waters worldwide with consequences for the health of marine ecosystems, but also for the livelihoods of fishers and local fishing communities. One of the many reasons for unsustainable use of marine resources is a non-transparent and top-down fisheries management. To address the deficiencies in achieving sustainable fisheries, the European Union increasingly adopts a holistic approach to the management of living marine resources through its Common Fisheries Policy (CFP), meaning ecosystem-based management that considers knowledge and social interactions among resource users and interest groups in decision- making processes. Nevertheless, differences in knowledge, but also values, norms and interaction with the system are a reason for different understanding regarding the functioning of a social-ecological system (SES) to which individuals and groups belong and can be a reason for profound conflicts. A very striking example in European fisheries is the management of Western Baltic (WB) cod (Gadus morhua), characterized by several management measures, including total allowable catch and marine protected area designation that met with varying levels of acceptance among the stakeholders involved. This thesis focuses on the WB cod fisheries in general and more explicitly on the resource users and interest groups involved in or affected by its management. Multiple methods were used to uncover the stakeholder network of WB cod fisheries, and to investigate the perceptions of different stakeholders on the system, as well as to explore the diverse knowledges about the system and to formulate ideas for a ‘alternative’ management. We first conducted a literature review with the objective of understanding the term ‘stakeholder’ and ‘participation’ in the context of coastal and marine fisheries (Study I). We found a strong increase in the number of projects in which ‘stakeholder participation’ was addressed. ...